Foreword - Strauss, D. F. M. (Koers, 2011)
Publishing a Festschrift in honour of the academic work of a colleague and fellow scholar certainly constitutes one of the most rewarding intellectual events such an academic can experience. Having the task to write a Foreword to this Festschrift is, therefore, in itself, also a special privilege.